Diseño de un plan de gestión de calidad e inspección en la construcción de subestaciones eléctricas - Suárez-Vargas, Pedro Luis (Instituto Tecnológico de Costa Rica, 2011)
This document contains the design of a System of Quality Control and Inspection in the Construction of Electrical Substations for the Instituto Costarricense de Electricidad, especially for Strategic Business Unit Transmission of Electricity in its Expansion Process Network (UEN TE). The main objective of this work is to update and improve existing construction specifications and undertake the design of a system of quality control and inspection for the construction of electrical substations. In order to achieve the stated objective, a series of interviews to engineering professionals were carried out, as well as field visits to the electricity substations throughout the country. This becomes the main source of information. As a result of this work, the System of Quality Control and Inspection in the Construction of Electrical Substations was obtained, which consists of a series of documents such as Electrical Substations Construction Requirements, Aspects of Building Design of Electrical Substations and checklist for Building Electrical Substations. With the design of System of Quality Control and Inspection it is ensured that the UEN TE has the necessary tools to control the quality of its electrical projects.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2011.
Keywords: Estandarización; Listas de Verificación; Inspección; Control